Menguji Kepastian Hukum Penyelesaian Perselisihan di Bidang Hilir Minyak dan Gas Bumi oleh Badan Pengatur - Dara Salsabila (Swara Patra, 2021)
The Agency's Governing Body downstream Oil and Gas has the authority to settle disputes as stated in the applicable laws and regulations. Optimizing the role of the Agency's Governing Body downstream Oil and Gas is important to ensure the continuity of good business operations in the downstream oil and gas sector. In addition, this process also aims to avoid disputes between business entities to enter the court, which requires a large amount of money, is a long process, and is a win-lose solution. With the existence of an alternative dispute resolution approach, it is hoped that disputes can be resolved in a friendly manner and ensure the confidentiality of business entities and promote a win-win solution. However, the problem is that the Regulatory Body does not yet have laws and regulations that regulate concretely the proceedings in the settlement of this dispute so that it implies the absence of legal certainty and good precedent for the Business Entity or the parties.